Long-term exposure to high-altitude hypoxic environments reduces blood pressure by inhibiting the renin-angiotensin system in rats - Duo, Delong; Zhu, Junbo; Wang, Mengyue; Wang, Xuejun; Qu, Ning; Li, Xiangyang (Frontiers in Physiology, 2025)
IntroductionThis study assesses the effects of chronic high-altitude hypoxia on blood pressure regulation in spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) rats, focusing on cardiovascular remodelling, hemodynamic alterations, and renin-angiotensin system (RAS) modulation.MethodsEight-week-old male SHR and WKY rats were divided into four groups: the SHR high-altitude hypoxia group (SHR-H), WKY high-altitude hypoxia group (WKY-H), SHR control group (SHR-C), and WKY control group (WKY-C). The hypoxia groups were exposed to 4,300 m (PaO2: 12.5 kPa) for 10 weeks. Blood pressure was measured via non-invasive tail-cuff method, cardiac function via echocardiography, and right heart pressures via catheterization. Histopathological analysis included haematoxylin and eosin and Masson/Weigert staining for organ damage and vascular remodelling, whereas RAS components were assessed using immunohistochemistry.ResultsThe results showed that chronic hypoxia significantly reduced systolic blood pressure, diastolic blood pressure, and mean arterial pressure in SHR-H rats, but not in WKY-H rats. SHR-H rats showed a reduced ejection fraction, fractional shortening, systolic left ventricular anterior wall thickness, and diastolic left ventricular anterior wall thickness, increased left ventricular diastolic diameter, and left ventricular systolic diameter, whereas WKY-H showed only ejection fraction and fractional shortening decline. Both groups developed elevated mean pulmonary arterial pressure, right ventricular systolic pressure, and right ventricular end-diastolic pressure. SHR-H rats displayed aortic medial thinning, elastic fibre degradation, increased blood viscosity, and multi-organ damage (myocardial necrosis, pulmonary fibrosis), whereas WKY-H rats showed medial thinning and erythrocyte hyperplasia without fibrosis. Immunohistochemistry revealed suppression of the angiotensin-converting enzyme (ACE)-angiotensin II (Ang II)-angiotensin II type I (AT1) axis in SHR-H, whereas WKY-H exhibited reduced Ang I/II without ACE2 and Mas receptor (MasR) changes.ConclusionLong-term hypoxic exposure at high-altitude reduces blood pressure in SHR rats, which may be attributed to a combination of cardiac functional compensation failure, vascular remodelling, and simultaneous inhibition of the ACE-Ang II-AT1R and ACE2-Ang1-7-MasR axes.